ECONOMIC DIVERSIFICATION IN RURBAN NANDURBAR: AN OVERVIEW - Manohar B. Patil, Dr. Sunil V. Kuwar, Dr. Uttam V. Nile (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2025)
Economic diversification is a key strategy for enhancing the sustainability and resilience of rural and semi-urban areas. Nandurbar, a district located in the northern part of Maharashtra, represents a rurban area-a region that exhibits both rural and urban characteristics. Traditionally dependent on agriculture, Nandurbar has witnessed a gradual shift towards diversification in recent years, with notable growth in industries and services. This paper aims to explore the factors driving economic diversification in Nandurbar, analysing changes in key sectors such as agriculture, small-scale industries, and services. Through the use of secondary data and qualitative analysis, the study examines the impact of infrastructure development, government policies, and local entrepreneurship on the diversification process. Government schemes like the National Rural Livelihood Mission (NRLM) and improvements in road connectivity, electricity, and water supply have played a crucial role in transforming the region’s economic landscape. Additionally, the paper highlights the role of small-scale agro-based industries and services in providing alternative sources of income and employment to the rural population. The research further investigates the challenges faced by Nandurbar in its journey toward economic diversification, including issues like limited access to capital, skill gaps, and market access for small businesses. The findings suggest that while the region has made significant strides in diversifying its economy, there is still potential for further growth, particularly in terms of industrial development and skill enhancement for the local workforce. This study concludes by offering recommendations to enhance economic diversification in Nandurbar, emphasizing the need for continued investment in infrastructure, support for local businesses, and targeted skill development programs. The insights from this research contribute to a deeper understanding of the dynamics of rurban economies and provide valuable lessons for other regions undergoing similar transitions.